PA.02 Tourettism in adults. Issue 8 (7th July 2011) - Maalik, M A; Stern, J S; Hafez, A; Simmons, H; Robertson, M M
Abstract : Aims: We investigated cases of Tourette syndrome (TS) with atypical chronology in terms of age of onset. According to DSM IV-TR onset of TS is by the age of 18. Most cases have their onset earlier at ages 5–10. Peak severity of tics is usually around the ages of 11–13 so that severe cases in adulthood represent a minority. We investigated the characteristics of patients (1) with an onset of symptoms in late adolescence (2) with apparent onset in adulthood and (3) other atypical cases with an early onset of mild symptoms followed by transition to significantly more severe tics after the age of 18. Methods: Review of 220 patient records collected in a joint paediatric and adult Tic Disorder clinic was performed. Cases with onset over the age of 18, or of onset from 15–18 years old, or of childhood onset with late significant exacerbation over the age of 18 were selected for comparison with the remaining majority of cases who exhibited early onset and had been seen either as paediatric or adult referrals. Phenomenology of the tics and associated comorbidities were examined. Results: Six adult-onset cases were identified and had a mean age of onset of 37.3 (21–57). Four were male and 4 had tics that were considered moderate or severe. None of these cases experienced premonitory sensations in association with their tics, a feature which is integral to most people with tics. Obsessionality milder than the criteria for OCD was present in half the cases, 2 had coprolalia, and a family history of tics was present in two cases only. There were also 6 "late exacerbation" cases with a mean age of 25 years for the exacerbation and all had severe tics and coprolalia as part of their late presentation. Most of these cases had a family history of tics or obsessionality and also significant histories of difficulties at birth/delivery. These cases all had premonitory sensations as would be expected from the control cases. Only four late adolescent-onset cases were found and, given the small number, they did not have features distinguishing them from control cases. Conclusions: It is suggested that adult-onset cases of a phenotype otherwise consistent with the TS phenotype may be biologically different to childhood-onset cases. We found an unusual absence of premonitory sensations in this group and also less relevant family history than expected. Adult-onset TS is documented here and previously only in small numbers. Some previous data has considered cases of a childhood-onset mild tic disorder followed by later severe exacerbation as an adult-onset category. We separated this group and found they experienced premonitory sensations as usual but all had a distinctively severe disorder with coprolalia.